Advances in Radiobiology of Stereotactic Ablative Radiotherapy - Qiu, Bin; Aili, Abudureyimujiang; Xue, Lixiang; Jiang, Ping; Wang, Junjie (Frontiers in Oncology, 2020)
Radiotherapy (RT) has been developed with remarkable technological advances in recent years. The accuracy of RT is dramatically improved and accordingly high dose radiation of the tumors could be precisely projected. Stereotactic radiosurgery (SRS) and stereotactic body radiotherapy (SBRT), also known as stereotactic ablative radiotherapy (SABR), are rapidly becoming the accepted practice in treating solid small sized tumors. Compared with the conventional fractionation external beam radiotherapy (EBRT), SABR with very high dose per fraction and hypo-fractionated irradiation yields convincing and satisfied therapeutic effects with low toxicity, since tumor cells could be directly ablated like radiofrequency ablation (RFA). The impressive clinical efficacy of SABR is greater than expected by the linear quadratic model and the conventional radiobiological principles, i.e. 4 R's of radiobiology (Reoxygenation, Repair, Redistribution, and Repopulation), which may no longer be suitable for the explanation of SABR’s ablation effects. Based on 4 R's of radiobiology, 5 R's of radiobiology emphases the intrinsic radiosensitivity of tumor cells, which may correlate with the responsiveness of SABR. Meanwhile, SABR induced the radiobiological alteration including vascular endothelial injury and the immune activation, which has been indicated by literature reported to play a crucial role in the tumor control. However, a comprehensive review involving these advances in SABR is lacking. In this review, advances in radiobiology of SABR including the role of 4 R's of radiobiology and potential radiobiological factors for SABR will be comprehensively reviewed and discussed.